Unusual Temperature Dependence of Bandgap in 2D Inorganic Lead‐Halide Perovskite Nanoplatelets. Issue 19 (11th August 2021) - Yu, Shaohua; Xu, Jin; Shang, Xiaoying; Ma, En; Lin, Fulin; Zheng, Wei; Tu, Datao; Li, Renfu; Chen, Xueyuan
Abstract: Understanding the origin of temperature‐dependent bandgap in inorganic lead‐halide perovskites is essential and important for their applications in photovoltaics and optoelectronics. Herein, it is found that the temperature dependence of bandgap in CsPbBr3 perovskites is variable with material dimensionality. In contrast to the monotonous redshift ordinarily observed in bulk‐like CsPbBr3 nanocrystals (NCs), the bandgap of 2D CsPbBr3 nanoplatelets (NPLs) exhibits an initial blueshift then redshift trend with decreasing temperature (290–10 K). The Bose–Einstein two‐oscillator modeling manifests that the blueshift‐redshift crossover of bandgap in the NPLs is attributed to the significantly larger weight of contribution from electron‐optical phonon interaction to the bandgap renormalization in the NPLs than in the NCs. These new findings may gain deep insights into the origin of bandgap shift with temperature for both fundamentals and applications of perovskite semiconductor materials. Abstract : The temperature dependence of bandgap in inorganic lead‐halide perovskites is found to be variable with material dimensionality. In sharp contrast to the monotonous redshift usually observed in quasi‐3D bulk‐like CsPbBr3 nanocrystals (NCs), the bandgap of 2D 2‐monolayer‐thick (2‐ML‐thick) CsPbBr3 nanoplatelets (NPLs) exhibits an initial blueshift then redshift trend with decreasing temperature (290–10 K).